Bioactive Phenolics of the Genus Artemisia (Asteraceae): HPLC-DAD-ESI-TQ-MS/MS Profile of the Siberian Species and Their Inhibitory Potential Against α-Amylase and α-Glucosidase - Olennikov, Daniil N.; Chirikova, Nadezhda K.; Kashchenko, Nina I.; Nikolaev, Vyacheslav M.; Kim, Sang-Woo; Vennos, Cecile (Frontiers in Pharmacology, 2018)
Artemisia genus of Asteraceae family is a source of medicinal plants known worldwide and used as ethnopharmacological remedies for the treatment of diabetes in Northern Asia (Siberia). The aim of this study was to determine the phenolic profile of twelve Siberian Artemisia species (A. anethifolia, A. commutata, A. desertorum, A. integrifolia, A. latifolia, A. leucophylla, A. macrocephala, A. messerschmidtiana, A. palustris, A. sericea, A. tanacetifolia, A. umbrosa) and to test the efficacy of plant extracts and pure compounds for antidiabetic potential. Finally, by HPLC-DAD-ESI-TQ-MS/MS technique, 112 individual phenolic compounds were detected in Artemisia extracts in a wide range of concentrations. Some species accumulated rare plant phenolics, such as coumarin-hemiterpene ethers (lacarol derivatives) from A. latifolia and A. tanacetifolia; melilotoside from A. tanacetifolia; dihydrochalcones (davidigenin analogs) from A. palustris; chrysoeriol glucosides from A. anethifolia, A. sericea and A. umbrosa; eriodictyol glycosides from A. messerschmidtiana; and some uncommon flavones and flavonols. The predominant phenolic group from Artemisia species herb was caffeoylquinic acid (CQAs), and in all species, the major CQAs were 5-O-CQA (20.28–127.99 μg/g) and 3,5-di-O-CQA (7.35–243.61 μg/g). In a series of in vitro bioassays, all studied Artemisia extracts showed inhibitory activity against principal enzymes of carbohydrate metabolism, such as α-amylase (IC50 = 150.24–384.14 μg/mL) and α-glucosidase (IC50 = 214.42–754.12 μg/mL). Although many phenolic compounds can be inhibitors, experimental evidence suggests that the CQAs were key to the biological response of Artemisia extracts. Mono-, di- and tri-substituted CQAs were assayed and showed inhibition of α-amylase and α-glucosidase, with IC50 values of 40.57–172.47 μM and 61.08–1240.35 μM, respectively, and they were more effective than acarbose, a well-known enzyme inhibitor. The results obtained in this study reveal that Siberian Artemisia species and CQAs possess a pronounced inhibitory activity against α-amylase and α-glucosidase and could become a complement to synthetic antidiabetic drugs for controlling blood glucose level.